Guideline of guidelines: urinary incontinence. (1st July 2015) - Syan, Raveen; Brucker, Benjamin M.
Abstract : The objective of the article is to review key guidelines on the management of urinary incontinence (UI) to guide clinical management in a practical way. Guidelines produced by the European Association of Urology (updated in 2014), the Canadian Urological Association (updated in 2012), the International Consultation on Incontinence (updated in 2012), and the National Collaborating Centre for Women's and Children's Health (updated in 2013) were examined and their recommendations compared. In addition, specialised guidelines produced by the collaboration between the American Urological Association and the Society of Urodynamics, Female Pelvic Medicine and Urogenital Reconstruction on overactive bladder and the use of urodynamics were reviewed. The Appraisal of Guidelines for Research and Evaluation II (AGREE) instrument was used to evaluate the quality of these guidelines. There is general agreement between the groups on the recommended initial evaluation and the use of conservative therapies for first‐line treatment, with a limited role for imaging or invasive testing in the uncomplicated patient. These groups have greater variability in their recommendations for invasive procedures; however, generally the mid‐urethral sling is recommended for uncomplicated stress UI, with different recommendations on the approach, as well as the comparability to other treatments, such as the autologous fascial sling. This 'Guideline of Guidelines' provides a summary of the salient similarities and differences between prominent groups on the management of UI.